Trials of biological control of Aonidiella aurantii Maskell (Hemiptera, Coccoidea) in citrus groves in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors report the results of field trials that assessed the potential of biological control of California red scale Aonidiella aurantii Maskell in citrus groves, using Aphytis melinus DeBach. The trials, performed under the P.O.M. project (Multi-regional operative project) A36, were carried out in 1999 - 2000 in five farms: three located in Sicily and two in Calabria. In each farm, three lots of 1 ha were established, two of which biologically treated and one acted as the control. Monitoring of A. aurantii male flight was achieved using California Citrus l.P.M.-type traps (one per lot) that were checked weekly and the dispensers were replaced monthly. Releases, six in all, started in April and continued to September, each time releasing 20,000 specimens/ha, for a total of 120,000 Aphytis/year/ha. The parasitization was assessed on 1 m of branches about 1 cm in diameter, taken from 4 plants within each lot, at the time of the third and sixth releases, and observing the specimens present. On commercial ripening, we assessed the percentage of infested fruits out of 100 fruits per treatment and the percentage of parasitization out of 500 scale specimens counted on 100 fruits picked from 5 infested plants. Data underwent statistical analysis (ANOVA). Results revealed no statistically significant differences in the treatments. In 60% of cases the percentage of fruits infested by the armoured scale were higher in lots in which A. melinus adult were released, with values varying between 39 to 77% in 1999 and 25 to 37% in 2000. On branches and fruits taken from these lots, in 2000, the parasitization rates were higher than those in the control areas (varying between 29.37 % to 46.84 %). Also in relation to the different levels of infestation of the trees, the parasitic activity of A. melinus was insufficient to limit damage by A. aurantii within economically viable limits.
Keywords: Aphytis melinus; augmentative release; armoured scale